THE EFFECTIVENESS OF USING INDEX CARD MATCH IN TEACHING VOCABULARY - Ariani, Sri; Setianingsih, Tri (IKIP Mataram, 2018)
This research aims to find out Is there any significant differences between the impact of traditional teaching method and using Index Card Match in teaching English vocabulary at the First Year Students of SMA HANG TUAH 3 MATARAM and to find out does using Index Card Match have a positive effect on students’ vocabulary knowledge. The sample of this research is 40 students. The kind of this research is experimental research. The students are divided into two groups such as experimental group and control group. Then the research subjects are pre-tested to know their prior vocabulary mastery. After the treatment, the sample is post-tested to know their recent vocabulary mastery as the result of the treatment. The scores in both pre-test and post-test are taken as the main data of the research. The data is analyzed by using t-test.